Qualitative and Quantitative Analysis of Changes in Saliva and Subjective Oral Dryness in Patients with Thyroid Disorders - Zhahid Hassan; Afreen Nadaf; Sonia Gupta (Asian Journal of Medical Research, 2019)
Background: The association of salivary function with numerous systemic illnesses has been stated by various researches. There is a strong relationship of salivary function with common illnesses like diabetes, oral submucous fibrosis, and asthma. Thyroid dysfunction are one of the most common endocrine disorders worldwide. Aims and objective: To determine the qualitative and quantitative changes in the salivary function in patients with thyroid dysfunction.Subjects and Methods:A cross-sectional study was carried out on 40 subjects, including 20 thyroid disorders patients and 20 control subjects. Unstimulated and stimulated salivary flow rates, pH, and buffering capacity of the whole saliva were determined as well as subjective oral dryness in the study subjects.Results:In the present study, a statistically significant decrease in salivary parameters such as buffering capacity and flow rates was seen. Subjective oral dryness was observed in affected patients.Conclusion: In the present study, a correlation between thyroid dysfunction and salivary gland function was observed in patients with thyroid disorders.